Teacher Performance: The role of Professional Competence and Satisfaction - Bob Foster (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
The phenomenon that occurs based on observations shows that teacher performance is not optimal; this is due to the presumption that professional competence and job satisfaction are not optimal. For this reason, this study aims to determine the influence of professional competence and job satisfaction on teacher performance. This study uses a survey approach method; the type of research is descriptive analysis—the data collection method done by interview, questionnaire, and documentation study. The data analysis method used is path analysis. This study's sample was 42 teachers in the Kindergarten Cluster in one of the districts in Bandung Regency. The results showed that professional competence and job satisfaction significantly affected teacher performance both simultaneously and partially. This result means that professional competence and job satisfaction can improve teacher performance.